Readiness of Prospective Teachers in Facing the Society 5.0 Era: A Study of Primary School Teacher Education Students at Universitas Muhammadiyah Prof. Dr. Hamka - Desak Made Darmawati; Nur Busyra; Muhamad Alimudin (Indonesian Journal Economic Review (IJER), 2026)
The rapid advancement of digital technology in the Society 5.0 era necessitates the preparation of prospective teachers who are capable of integrating technological innovation with human-centered educational values. This study aims to analyze the readiness of prospective teachers in facing the challenges of Society 5.0, focusing on students of the Primary School Teacher Education Program (PGSD) at the Faculty of Teacher Training and Education, Universitas Muhammadiyah Prof. Dr. Hamka. Employing a quantitative approach with a descriptive survey design, data were collected through structured questionnaires distributed to undergraduate students. The instrument measured dimensions of readiness, including technological competence, pedagogical competence, professional competence, digital literacy, 21st-century skills, and humanistic values. The collected data were analyzed using descriptive statistics and inferential analysis with the assistance of Statistical Package for the Social Sciences (SPSS). The findings reveal that prospective teachers demonstrate a very high level of readiness to face the Society 5.0 era. Technological competence and digital literacy were identified as significant contributors to teacher preparedness. These results indicate that teacher education programs play a crucial role in equipping future educators with the competencies required to adapt to digital transformation while maintaining ethical and professional standards. The study contributes to the theoretical development of teacher readiness and provides practical implications for curriculum innovation and policy formulation in higher education.